Circulares de cordón umbilical: Factores de riesgo materno. Hospital de Apoyo de Iquitos “César Garayar García” - Lozano Amasifén, Victor Raúl (1995)
We report the study of 598 consecutive deliveries of viable children who produced 170 umbilical cord births, with an incidence of 28.42%. The age of the parturients was more frequent between 15 and 19 years of age with 33.53% (P <0.10). Regarding the place of origin, 50% of the pregnant women come from rural areas (P <0.01). The level of primary education was the most frequent with 55.88% (P <0.10). The single marital status reached the highest percentage 52.35% (P <0.30). Parity in the study group, obtained the highest percentage in primiparous women with 51.18% (P <0.50). Regarding gestational age, 60% were present between 37 and 38 weeks of gestation (P <O.O1). The number of external abdominal massage performed by empirical midwife was very high in the study group 85.3% (P <0.01). Apgar at the first minute with score 2-6 was high the circular group with a presentation frequency of 40.59% (P <0.01). The most frequent circular type was around the fetal neck 93.54%, of which the circular simple to the neck 65.89% and 27.65% circular double to the neck.